2012
DOI: 10.1364/oe.20.007777
|View full text |Cite
|
Sign up to set email alerts
|

Modeling nonlinearity in coherent transmissions with dominant intrachannel-four-wave-mixing

Abstract: By extending a well-established time-domain perturbation approach to dual-polarization propagation, we provide an analytical framework to predict the nonlinear interference (NLI) variance, i.e., the variance induced by nonlinearity on the sampled field, and the nonlinear threshold (NLT) in coherent transmissions with dominant intrachannel-four-wave-mixing (IFWM). Such a framework applies to non dispersion managed (NDM) very long-haul coherent optical systems at nowadays typical baudrates of tens of Gigabaud, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…The first one evaluates the integral in closed-form over the distance, leaving a double integral over the frequency domain [6], [23], [28] …”
Section: A Numerical Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…The first one evaluates the integral in closed-form over the distance, leaving a double integral over the frequency domain [6], [23], [28] …”
Section: A Numerical Implementationmentioning
confidence: 99%
“…Several analytical models for performance evaluation and design of such systems have been proposed [6]- [10], which all share the same underlying basic assumption that nonlinearity is a small perturbation of the nonlinear Schrödinger equation (NLSE) of propagation. Among these, the GN model developed in [8], [10] is particularly attractive since it is able to provide a Manuscript received July 11, 2013; revised September 24, 2013; accepted September 28, 2013.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This nonlinear noise can be described as a Gaussian noise [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], at least in dispersion uncompensated (DU) coherent systems. Gaussian nature of the nonlinear interference (NLI) noise fields is conditioned by Gaussian distribution of the information sampled signal [4][5][6][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In the UT scenario, it has been shown that one possible way of modeling the effect of fiber nonlinearity is to approximate its impact as an additive Gaussian disturbance [1][2], called nonlinear interference (NLI). Several non-linear propagation models are available that allow to estimate the power of the NLI produced in a given link, among which [3][4][5][6][7][8][9]. In particular, [3][4], [6], [8][9] provide rather similar results.…”
Section: Introductionmentioning
confidence: 99%